Impact of COVID-19 on agricultural trade, economic activity, and poverty in Africa - Seck, Abdoulaye (2021)
Abdoulaye Seck POLICY SEMINAR Making the most of intra-African trade: the 2021 Africa Agriculture Trade Monitor Co-Organized by IFPRI and AKADEMIYA2063 SEP 23, 2021 - 09:30 AM TO 11:00 AM EDT